The Efffects of the Rupnik Scandal on Slovenian Catholics - Smrke, Marjan (Occasional papers on religion in Eastern Europe, 2024)
At the end of 2022, Slovenia and the Catholic world were shocked by news of the inappropriate sexual behavior of the globally successful sacral artist Father Marko Ivan Rupnik. In 2023, after additional accusations of (former) nuns of the Slovenian based female Loyola Community, Rupnik was expelled from the Jesuit Order and the Loyola Community dissolved. In this discussion, I will present the impact of the scandal on Slovenian Catholics. An analysis of posts posted on ten Catholic websites reveals nine types of responses: silence; denial or conspiracy theories; relativization; justification of Rupnik’s behavior; fortress mentality; deep disappointment; regret over the lack of vigilance; claims of systemic lack of responsiveness on the part of the Church; accusations of Rupnik’s alleged Protestant heresy, and demand for the removal of his mosaics from holy sites. Some of these effects could be described as hair-line fractures in the Slovenian Catholic body, others as more serious breaks. In this context, it is surprising that the scandal had no effect on the trajectory of statistics collected on religion, which have shown a decline in Slovenia since 2011. In my concluding reflections, I discuss the scandal as a phenomenon that is a consequence of the specific and still problematic relationship of the Catholic Church to sexuality.